HEALTH PROMOTION ANALYSIS AND SIMULATION ON INCREASING VACCINATION WITH USING THE SRV MODEL IN PINRANG DISTRICT - Side, Syafruddin; Sanusi, Wahidah; Padjalangi, Andi Muhammad Ridho Yusuf Sainon Andi; Pratama, Muhammad Isbar (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2023)
This study discusses the SRV mathematical model of the rate of people refusing vaccination. The data used is primary data in the form of questionnaire data taken directly from the community in Pinrang district related to the rate of people who refuse vaccination. This research starts from building an SRV model to then perform an analysis and simulation of increased vaccination as a result of the role of the Health Promotion section, determining the balance point, analyzing the stability of the model, determining the value of the basic reproductive number (R0), conducting model simulations using Maple21 software, and interpreting the simulation results. . In this article, a mathematical model of SRV is obtained from the analysis and simulation of increased vaccination as the role of the Health Promotion section; two balance points, namely the free balance point to refuse vaccination and the balance point to refuse vaccination; and the basic reproduction rate R0=0.44721 indicates that the population refuses vaccination is decreasing.